The Most Abundant Ferns in Utilization Block of Sumber Agung Resort Bandar Lampung Taman Hutan Raya Wan Abdul Rachman Lampung - Zarkoni Zarkoni; Yulianty Yulianty; Bambang Irawan; Suratman Suratman (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
Taman Hutan Raya Wan Abdul Rachman (Tahura WAR) is a protected forest area and habitat for various types of plants and animals. Tahura WAR is an area that has a high diversity of ferns, ferns are quite heterogeneous plants both in terms of habitat and way of life, ferns are one group of vascular plants that have a fairly high number of species, live in nature, some are attached to tree trunk (epiphyte) or grow on the ground. This research was carried out in the utilization block of Sumber Agung, which focused on fern species diversity, diversity, dominant species, and descriptions of types of ferns. This research was carried out by direct observation based on the existence of all types of ferns that are considered to represent the place. Based on observations in general, ferns are composed of 37 species, 28 genera, and 14 families. The highest number of ferns is Polypodiaceae with 8 species. With the Shannon-Wienner (H') diversity index of H’= 2.9. Type N. acutifolia dominates this research area with an INP value of 25.8%.